Cascading feeder vessels and the rationalisation of small container ports. (February 2017) - Monios, Jason
Abstract: Small container ports rely on feeder services from hub ports to provide access to unitised trade flows for their hinterlands. They generally possess limited water depth and handling facilities, as investments required to handle larger vessels are not justified by their low container throughput. This paper questions the future of small ports due to larger vessels cascading down as a result of ever-larger vessels on the major trade lanes. The paper uses vessel call data to identify all world ports currently served by sub-1000 TEU vessels. Data on the dimensions of the vessel fleet and order book are analysed in conjunction with accessibility constraints at these small ports. Results show that with 15% of the sub-1000 TEU fleet currently laid up and very few on order, larger feeders with deeper drafts seem certain to serve at least some of these routes. But with 90 container ports (21%) having berth depth of less than 9.1 m and the need to accommodate design drafts of at least 8.7 m, larger vessels will threaten the viability of these ports unless they commit significant investment. A geographical analysis is also conducted, mapping the distribution of small ports across the globe and classifying coastal, estuary, river and island locations, as well as identifying clusters of small ports that could in future be served by second-tier hubs, such as Southeast Asia and the Baltic Sea. Findings suggest that, just as container ports at the larger end of the scale were rationalised as flows concentrated at major hubs, several drivers exist for the same process to occur at small ports. Consequently, the paper asks how small ports and local shippers will cope, whether such ports lose their connections entirely, if local shippers must pay for an additional handling cost to tranship a second time from large feeder to small feeder, or whether they rely on overland transport links.